Electromagnetic flux analysis on a new outer-rotor hybrid excitation flux switching machine - Ahmad, Md Zarafi (2014)
This paper presents an analysis of electromagnetic flux capability on a new 12Slot-14Pole outer-rotor hybrid excitation flux switching machine (ORHEFSM). In this proposed machine, all the magnetic flux sources are placed on the stator resulting for robust machine and suitable for high speed application. Moreover, coil test analysis, permanent magnet (PM) and DC field excitation coil (FEC) flux characteristic, flux interaction between DC FEC and armature coil, flux distribution, and torque characteristics are also investigated. The results show that the torque performance of the proposed machine is proportional to the change of flux linkage. Therefore, a flux control capability of the machine gives additional advantage for variable speed condition application.